Evaluation of oral health status in the population above 50: evidence from the ardakan cohort study on aging (ACSA) - Ahmad Delbari; Fatemeh Ghavidel; Vahid Rashedi; Mohammad Bidkhori; Mohammad Saatchi; Elham Hooshmand (BMC Oral Health)
Abstract Background The global population is undergoing rapid aging, and older individuals are more susceptible to various health issues, including oral health problems. Despite the increasing attention given to healthy aging, oral health has often been overlooked in discussions related to health problems. This study aims to assess the oral health status of middle-aged and older adults in Iran. Methods This cross-sectional study analyzed data from 4970 men and women aged 50 years and above, who participated in the Ardakan Cohort Study on Aging (ACSA) between 2020 and 2022. Trained personnel administered a questionnaire and conducted oral health examinations to determine the oral health status and oral hygiene behaviors of the participants. Results The mean value (SD) of the total Decayed, Missing, and Filled Teeth (DMFT) index was 21.3 (10.7). Approximately 46% of all participants were completely edentulous (without natural teeth). Moreover, 58.5% of the total sample wore dentures, and the mean age (SD) when they started using dentures was 48.5 (20.7) years. About 71% of participants with natural teeth reported brushing their teeth at least once a day, while about 63% of denture wearers cleaned their dentures daily. In the sample, 28% of individuals had visited a dentist in the last year. The prevalence of difficulty in biting and chewing food among the participants was 48.2% and 44.6%, respectively. Additionally, nearly 68% of all samples reported experiencing at least one difficulty in daily functioning due to oral/dental conditions. The study identified cutoff points of seven (sensitivity = 56.8 and specificity = 77.5) and 10 (sensitivity = 72.1 and specificity = 71.1) missing teeth, indicating the presence of at least one problem in daily functioning due to oral/dental conditions in middle-aged and older adults, respectively. Conclusion The study reveals a high prevalence of edentulism and denture use among participants aged 50 years and above. The majority of samples reported difficulties in daily functioning due to oral and dental conditions, especially in biting and chewing food. These findings highlight the importance of proactive measures to address oral health issues in middle-aged and older adults, thereby enhancing their overall health and well-being.